Testing the transport energy-environmental Kuznets curve hypothesis in the EU27 countries - Pablo-Romero, M.P. (2017)
Transport activities are essential for economic and social development. Nevertheless, the transport sector has also shown the fastest growth in energy consumption in the European Union and its contribution to increasing greenhouse gas emissions merits the thorough attention of academics and policy makers. In this paper we analyze the relationship of economic growth and transport activities with transport final energy consumption. Energy Kuznets curves are estimated for a panel data set covering the EU27 countries in the period 1995–2009 for total transport energy use, household transport energy use, and productive transport energy use (all three in absolute and per capita energy use terms). The productive transport energy use and gross value added relationship are further considered as per hour worked. Finally, the control variables of energy prices and differences in the economic structures are tested. Empirical results show that the elasticity of transport energy use with respect to gross value added in per capita terms decreases from a threshold for the three transport energy consumption variables, but the turning point of improved environmental quality is not reached in any instance.